Needs Analysis Using LMS Digital Marketing to Improve Digital Literacy of Micro Small Medium Enterprises (MSME) - Erycha Arsita Devi; Sarwanto Sarwanto; Fatma Sukmawati (Universitas Sebelas Maret, 2023)
Digital literacy is the capacity to use a variety of media for information access, analysis, and production, in this case for participants in the economy. In order to increase the digital literacy of UMKM actors, it is necessary to design learning media formulations that address the following issues: 1) a description of how LMS on Digital Marketing is used as a learning tool for UMKM actors, 2) viewpoints on and challenges faced by UMKM players in the field, and 3) learning media formulations that are needed. The observations' findings took the form of a tool for UMKM actors to assess their needs, which was then subjected to descriptive qualitative analysis. Researchers discovered that social media has been used as a learning tool in the field to help people comprehend digital literacy. but has not been implemented optimally, namely: 1) there are obstacles in delivering material, especially material that cannot be observed directly or abstractly, 2) material is too abstract becomes difficult in delivery, UMKM actors need media that can visualize detailed and correct digital literacy so that there are no misunderstandings about digital literacy, and 3) learning media that needs to be developed to increase digital literacy of UMKM actors is LMS Digital Marketing.